Pemanfaatan Aplikasi Playstore Untuk Praktikum Pengukuran Pada Mata Pelajaran Fisika Siswa Kelas X - Dahrin, yusdarina; Napsawati; Idamayanti, Reski; Salim, Agus (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2023)
This implementation of Community Service aims to educate students in carrying out practicum activities, especially basic measurement practicums using the Palystore application. The training and mentoring was attended by 25 class Through this service activity, students feel very helpful in understanding the material as well as getting a visualization of the measurement concept in digital form. In operation, students can directly try to use measuring instruments, guess measurement results and are encouraged to think more critically so that the table data in the practical report can be filled in properly and correctly.